Agama dan Kesadaran Menjaga Lingkungan Hidup - Safrilsyah Safrilsyah; Fitriani Fitriani (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Religion and environment are seen as separated and unrelated discourses.  This understanding positions religion to unlikely give any contribution in enhancing  Muslims awareness on environment. Actually, in Islamic concept, the Quran  frequently mentions environment in different ways as a basic conception on  environment. At least there are three concepts introduced by the Quran; al-bi’ah, al- mubahat, marafiq al-balad. Al-bi’ah (occupying a territory, life space and  environment) perceives environment as a living space especially for humankind.  Through the concept of Muhabat, Islam treats forest ecosystem as a free space. There  are two categories in this concept. Firstly, environment is seen as a death earth (al- mawat) if the forests are wild jungles and remote from human territories. When the  forests are geographically around human territories, so they fall under the second  category that is marafiq al-balad (edge earth). This article explores the Islamic  concept on environment which is introduced by contemporary Muslim scholar, Yusuf  al-Qardhawi. According to him, there are some concepts in Islam that are related to  protecting environment. These concepts are of al-istishlah (shared benefit), maqashid  al-syari’ah, and Sunnah. This article is also enriched by Fitri’s thesis that explores  the role of religion and the awareness to protect environment in Simpang Tiga sub-disctict, Pidie of Aceh province. Her research finds that some of community religious  activities are not correlative with the awareness in protecting environment.